Iodine and other factors associated with fertility outcome following oil-soluble contrast medium hysterosalpingography: a prospective cohort study - Mathews, Divya M.; Peart, Jane M.; Sim, Robert G.; Johnson, Neil P.; O’Sullivan, Susannah; Derraik, José G B; Hofman, Paul L. (Frontiers in Endocrinology, 2024)
Objective: To examine factors associated with fertility following hysterosalpingography (HSG) using an oil-soluble contrast medium (OSCM). Design: In a prospective cohort study on 196 women having OSCM HSG, we showed that iodine excess was almost universal (98%) and mild subclinical hypothyroidism was frequent (38%). Here, we report the analyses of secondary outcomes examining factors associated with the likelihood of pregnancy following the HSG. Setting: Auckland, New Zealand (2019–2021) Sample: 196 women with primary or secondary infertility and underwent OSCM HSG Methods: Baseline and serial urine iodine concentrations (UIC) and thyroid function tests were measured over six months following the HSG. Pregnancy and treatment with levothyroxine during the study period were documented. Results: Following OSCM HSG, pregnancy rates were 49% in women aged <40 years (77/158) but considerably lower (16%) among those ≥40 years (6/38). Similarly, live birth rates were markedly lower in women ≥40 years (17%; 1/6) versus <40 years (73%; 56/77). 29% of participants were iodine deficient at baseline despite advice suggesting iodine fortification. Following HSG, women with moderate iodine deficiency had higher pregnancy rates than those with normal iodine levels (64%; p=0.048). Among women aged <40 years who had subclinical hypothyroidism (n=75), levothyroxine treatment was associated with higher pregnancy rates compared to untreated women [63% (26/48) vs 37% (10/27), respectively; p=0.047]. Conclusions: OSCM HSG was associated with higher pregnancy rates in women ≤40 than in those aged >40 years. Iodine deficiency was relatively common in this cohort, and increased iodine levels from OSCM exposure may contribute to the improved fertility observed with this procedure.